Geochemical characteristics of surface waters and groundwaters in the Velenje Basin, Slovenia - Tjaša Kanduč; Sergej Jamnikar; Jennifer McIntosh (Geologija, 2010)
The geochemical and isotopic composition of surface water and groundwaters in the Velenje Basin, Slovenia,were investigated to gain a better understanding of the origin of surface and groundwaters. Surface waters andgroundwaters from the Triassic aquifer are dominated by HCO3-, Ca2+, and Mg2+ from dissolution of carbonate minerals,while groundwaters from the Pliocene and Lithotamnium aquifers have distinct geochemical signatures,enriched in Na+ and K+. Surface waters are controlled by calcite dissolution, while groundwaters from the Triassicaquifer are controlled by dolomite dissolution. The partial pressure of CO2 in surface waters and groundwaters iswell above atmospheric concentrations, indicating that these waters are a potential source of CO2 to the atmosphere.The δ13CDIC values of surface waters are shown to be controlled by biogeochemical processes in the terrestrial environment,such as dissolution of carbonates, degradation of organic matter, and exchange with atmospheric CO2,which is more pronounced in the lake waters. The δ13CDIC values of groundwater from the Triassic aquifer are consistentwith degradation of CO2 and dissolution of dolomite. Groundwaters from the Pliocene and Lithotamniumaquifers have δ13CDIC values suggestive of biogenic CO2 reduction and degradation of organic matter.